Performance Analysis of Turbo Codes Using CRC and FC with OFDM - Vasuki, A; Kavitha, K; Sowndharya, G (International Journal of Computer Sciences and Engineering, 2025)
Long Term Evolution (LTE) is an evolving wireless communication standard that requires high data rate, higher bandwidth efficiency and better coverage. So, spectrally efficient techniques like Orthogonal Frequency Division Multiplexing (OFDM), Multiple Input Multiple Output and Error Control Codes with high coding gain are constituents of LTE. OFDM partitions a channel with wide bandwidth into several channels with narrow bandwidth that are flat, in order to mitigate the effects of multipath fading and Inter Symbol Interference (ISI). Error control codes enhance reliable transmission over noisy fading channels. The objective of this work is to increase data rate and reduce bit error rate by combining OFDM and Turbo Codes. Bit error rate is further reduced by applying Cyclic Redundancy Check (CRC) and Flip and Check algorithm (FC) along with turbo codes. In this paper, MAP and MAX Log MAP algorithms have been applied in the turbo decoding process and their performance compared. The proposed algorithm has been implemented and simulated using MATLAB.